2022
DOI: 10.3389/fonc.2022.914593
|View full text |Cite
|
Sign up to set email alerts
|

Non-Coding RNAs and Oral Cancer: Small Molecules With Big Functions

Abstract: Oral cancer remains a major public concern with considerable socioeconomic impact in the world. Despite substantial advancements have been made in treating oral cancer, the five-year survival rate for oral cancer remained undesirable, and the molecular mechanisms underlying OSCC carcinogenesis have not been fully understood. Noncoding RNAs (ncRNAs) include transfer RNAs (tRNAs), as well as small RNAs such as microRNAs, and the long ncRNAs such as HOTAIR are a large segment of the transcriptome that do not have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 278 publications
(357 reference statements)
0
23
0
Order By: Relevance
“…Some lncRNAs are responsible for the regulation of mRNA expression via binding to miRNAs and act as competitive endogenous RNAs 50,51 . In this research, a reverse correlation was observed between PVT‐1 and miR‐34a ( r = −0.52, p < 0.0001, Figure 3C).…”
Section: Resultsmentioning
confidence: 50%
“…Some lncRNAs are responsible for the regulation of mRNA expression via binding to miRNAs and act as competitive endogenous RNAs 50,51 . In this research, a reverse correlation was observed between PVT‐1 and miR‐34a ( r = −0.52, p < 0.0001, Figure 3C).…”
Section: Resultsmentioning
confidence: 50%
“…They regulate the transcription and translation in prokaryotic and eukaryotic organisms [ 1 ] by inhibiting specific genes at the transcriptional or translational level [ 2 ]. sRNAs are associated with cell growth, differentiation, cell death, and cellular defense in eukaryotes [ 3 ] and the biotic and abiotic stress response in prokaryotes and eukaryotes.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, miRNAs play a critical role as regulators in almost all biology, including normal physiological and pathological processes, most notably cancer. It is accepted that miRNAs are crucial for preventing the growth and spread of cancer [ 19 – 21 ]. Additionally, increasing evidence suggests that the circRNA/lncRNA-miRNA-mRNA regulatory axis controls how oral cancer spreads [ 22 26 ].…”
Section: Introductionmentioning
confidence: 99%